2020
DOI: 10.1108/ijoa-10-2019-1909
|View full text |Cite
|
Sign up to set email alerts
|

Expat or citizen? Raising the question of a potential impact of status on leader behavior

Abstract: Purpose The purpose of this study is to explore the concept that expatriate status, as opposed to national citizen status, may impact leader behavior. The intention is not to pursue a research question carved out from the expatriation and leadership research streams but rather to raise the issue of non-citizenship status as potentially moderating leader behavior. Design/methodology/approach The authors used grounded theory methodology, including interviews to gather data on the behavior of non-citizen leader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Authentic leadership would be more effective when the followers responded positively and significantly because committed employees were always the priority of the organization. However, this study uses a factor of organizational commitment named affective commitment that signifies the strongest thinking and attachment of followers to an organization (Goby and Alhadhrami, 2020) because this factor is more effective than normative and continuance commitment (Baek et al , 2019). Accordingly, the researchers revealed that authentic leadership psychologically strengthens affective organizational commitment in the tourism industry of Iran (Hadian Nasab and Afshari, 2019), in the Nursing context in Canada (Baek et al , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Authentic leadership would be more effective when the followers responded positively and significantly because committed employees were always the priority of the organization. However, this study uses a factor of organizational commitment named affective commitment that signifies the strongest thinking and attachment of followers to an organization (Goby and Alhadhrami, 2020) because this factor is more effective than normative and continuance commitment (Baek et al , 2019). Accordingly, the researchers revealed that authentic leadership psychologically strengthens affective organizational commitment in the tourism industry of Iran (Hadian Nasab and Afshari, 2019), in the Nursing context in Canada (Baek et al , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Affective organizational commitment may have a substantial impact on tacit knowledge sharing behavior (Baek et al , 2019) so, should be tested in sharing tacit knowledge sharing through the motivation of leaders at educational institutions (Al-Mutairi et al , 2020). Leaders can increase the performance of the employees (Thuan, 2020), particularly when the followers remain committed to the organization, and prioritize their physical attachment to an organization (Goby and Alhadhrami, 2020). Interestingly, ethical leadership is the key to scrutinize emotional attaching (affective organizational commitment) in turn, enhances task performance and reduces turnover intention of the followers in the diversified context in South Africa (Lee et al , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful localization should be considered as one of the main challenges for many governments and international companies in the GCC countries (Harry, 2007) including Oman. Therefore, the Omani government set quotas for various industries to determine the percentage of Omani to foreign workers (Goby & Alhadhrami, 2020). However, the success of these plans was limited as 85% of the workforce in private sectors is occupied by expatriates (Al-Lamki, 2005).…”
Section: Omanizationmentioning
confidence: 99%